Face Recognition System using Modular Principal Component Analysis - Sundarsingh, SP; Daniel Dharamaraj, CD (International Journal of Computer Sciences and Engineering, 2025)
This paper aims to present face recognition based on Principal Component Analysis (PCA) and Modular Principal Component Analysis (MPCA) approach. The PCA based face recognition method is not very effective under the conditions of varying poses and expressions rather than the proposed MPCA method. In the MPCA method the original face image was partitioned into tiny sub-images and then PCA technique is applied for each sub-image. Since a few of the normal facial features of an individual do not differ even when the pose and expression may differ, the proposed method manages these variations and takes only a few numbers of principal components for matching the faces for similarity. The proposed method improves the recognition rates with less number of principal components when compared with the conventional PCA method. This present system is tested with two standard face databases and results are presented.